2016
DOI: 10.1155/2016/3162743
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells Regulate the Innate and Adaptive Immune Responses Dampening Arthritis Progression

Abstract: Mesenchymal stem cells (MSCs) are multipotent stem cells that are able to immunomodulate cells from both the innate and the adaptive immune systems promoting an anti-inflammatory environment. During the last decade, MSCs have been intensively studied in vitro and in vivo in experimental animal model of autoimmune and inflammatory disorders. Based on these studies, MSCs are currently widely used for the treatment of autoimmune diseases such as rheumatoid arthritis (RA) characterized by complex deregulation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 125 publications
0
28
0
Order By: Relevance
“…In the last few years, many studies tried to clarify the role of MSCs in inflammatory processes. It has been seen that MSCs can modulate the cells of the innate and adaptive immune system by secreting cytokines [33]. In this scenario, the expression and secretion of selected inflammatory cytokines such as IL1A, IL1B, IL4, IL6, IL8, IL12, TNF-α, and G-CSF were analyzed in C-MSCs, IPF-MSCs, and NHLF before and after co-cultures.…”
Section: Discussionmentioning
confidence: 99%
“…In the last few years, many studies tried to clarify the role of MSCs in inflammatory processes. It has been seen that MSCs can modulate the cells of the innate and adaptive immune system by secreting cytokines [33]. In this scenario, the expression and secretion of selected inflammatory cytokines such as IL1A, IL1B, IL4, IL6, IL8, IL12, TNF-α, and G-CSF were analyzed in C-MSCs, IPF-MSCs, and NHLF before and after co-cultures.…”
Section: Discussionmentioning
confidence: 99%
“…MSCs spontaneously differentiate into chondrocytes and osteocytes and, at the same time, are able to suppress pathogenic immune response in inflamed synovial tissue . Therefore, during the last decade, therapeutic potential of MSCs in cell‐based therapy of RA and OA have been intensively explored in animal and clinical trials . Several lines of evidence suggested crucially important role of MSC‐derived IL‐1Ra for chondrogenic and osteogenic potential of MSCs and for MSC‐based alleviation of joint inflammation …”
Section: Therapeutic Potential Of Il‐1ra Producing Mscs In the Treatmmentioning
confidence: 99%
“…71 Therefore, during the last decade, therapeutic potential of MSCs in cell-based therapy of RA and OA have been intensively explored in animal and clinical trials. 72,73 Several lines of evidence suggested crucially important role of MSC-derived IL-1Ra for chondrogenic and osteogenic potential of MSCs and for MSC-based alleviation of joint inflammation. 69,74,75 Lee and coworkers demonstrated that MSCs (5 × 10 6 cells, intraperitoneally injected on Days 0 and 43) significantly alleviated synovial inflammation and cartilage destruction in IL-1RaKO mice.…”
Section: Il-1ra-expressing Mscs As a New Therapeutic Agent In The Cmentioning
confidence: 99%
“…The more recent but not the least documented anti‐inflammatory and immunoregulatory functions of MSC represent a huge interest in clinic for the treatment of inflammatory and autoimmune diseases 1,4,5 . Indeed, MSC have been described to repress the function of most, if not all, pro‐inflammatory immune cells including Th1 and Th17 lymphocytes while inducing the generation of regulatory T cells in vitro and in vivo (for review see 6). Although considered as candidate of choice for diverse therapeutic applications, MSC are highly plastic and consequently, their phenotype and functions are molded by factors present in their microenvironment including the pro‐inflammatory cytokines tumor necrosis factor α (TNFα) and Interferon gamma γ (IFNγ).…”
Section: Introductionmentioning
confidence: 99%